2015
DOI: 10.1038/ni.3108
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory microenvironments within the intestine regulate the differentiation of tissue-resident CD8+ T cells responding to infection

Abstract: We report that oral infection with Yersinia pseudotuberculosis (Yptb) results in development of two distinct populations of pathogen-specific CD8 tissue-resident memory T (TRM) cells in the lamina propria (LP). CD103– T cells did not require transforming-growth factor-β (TGF-β) signaling, but were true resident memory cells. Unlike CD103+ CD8 T cells, which were TGF-β-dependent and scattered in the tissue, CD103– T cells clustered with CD4 T cells and CX3CR1+ macrophages and/or dendritic cells around areas of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
275
2
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(304 citation statements)
references
References 53 publications
16
275
2
11
Order By: Relevance
“…[26][27][28][29][30][31][32][33] Recently, CD103 was identified as a surface marker of CD8 + tissue-resident memory T cells in many infectious diseases. [34][35][36] It is possible that these other immune cells could be depleted by anti-CD103-saporin. However, in this study, we found that nearly 90% of CD103 was expressed by CD11c + DCs in normal and AN kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33] Recently, CD103 was identified as a surface marker of CD8 + tissue-resident memory T cells in many infectious diseases. [34][35][36] It is possible that these other immune cells could be depleted by anti-CD103-saporin. However, in this study, we found that nearly 90% of CD103 was expressed by CD11c + DCs in normal and AN kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…While the chemokine receptor CXCR4 and the transcription factor KLF2 regulate T cell migration and memory formation (52)(53)(54)(55)(56), their downregulation is one of the hallmarks of ILC1s and ILTC1s (24). CD8 bright and CD8 dim T cells are not only metabolically dissimilar as described in murine studies (57, 58), but they may also have significantly distinct migratory and memory potential.…”
Section: Consistent With Our Findings Are Reports That Cd8mentioning
confidence: 99%
“…Such dissociation from the recirculating memory pool is seen during latent HSV infection (85), which is also likely to feature Ag expression that is too low for the activation and recruitment of circulating T cells (86). In addition, this specialization probably extends to the final stages of cleared infection, when pathogen load has declined to otherwise undetectable levels (40,58). The combination of local immune surveillance in low-inflammatory settings brings into play other scenarios, such as infection with commensal microorganisms.…”
Section: T Rm Cells Are Specialized For the Control Of Sequestered Pmentioning
confidence: 99%
“…Despite the strong association of this marker with the T RM cell subset, there is mounting evidence that not all T RM 2 T cells can also persist in tissues for prolonged periods (43,58), meaning that these are bone fide T RM cells. For CD4 + T RM cells, it would appear that CD103 is not an absolute marker for residency, because at least some tissueegressing CD4 + T cells express this molecule (13).…”
Section: Differences Between Cd4 and Cd8 T Rm Cellsmentioning
confidence: 99%